A Vinylene‐Bridged Conjugated Covalent Triazine Polymer as a Visible‐Light‐Active Photocatalyst for Degradation of Methylene Blue. Issue 7 (25th February 2020) - Xu, Chen; Xie, Qiujian; Zhang, Weijie; Xiong, Shaohui; Pan, Chunyue; Tang, Juntao; Yu, Guipeng
Abstract: The development of new photocatalytic platforms using novel semiconductor material is an important challenge. Herein, a sp 2 carbon‐conjugated covalent triazine polymer (sp 2 c‐CTP‐4), featuring a vinylene bridge and extended π‐conjugation, is prepared as a highly efficient photocatalyst for degradation of methylene blue. sp 2 c‐CTP‐4 exhibits substantial semiconducting properties such as enhanced charge transfer and prolonged lifetime of carriers compared to its counterparts with CN or CC connections, likely due to its extended π‐delocalization with an unencumbered CC bridge. Moreover, benefiting from its high chemical stability, the as‐made catalyst can be recycled five times with good retention of photocatalytic activity. This study provides a new pathway for constructing a robust platform for efficient photocatalysis and gives insight into the structure–property relationship of conjugated polymers. Abstract : A vinylene‐bridged conjugated covalent triazine polymer (sp 2 c‐CTP‐4) is developed as a stanchly photocatalytic scaffold for efficient degradation of methylene blue, and the catalyst exhibits good recyclability in the photodegradation. A series of elaborate comparisons are performed between sp 2 c‐CTP‐4 and its C–N and C–C bridged counterparts to give insight into the structure–property relationship of conjugated polymers.